2015
DOI: 10.1088/1367-2630/17/3/033010
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent pair dispersion in the presence of gravity

Abstract: Turbulent pair dispersion of heavy particles is strongly altered when particles of two different Stokes numbers (bidisperse) are considered, and this is further compounded when a uniform gravitational acceleration is present. Lagrangian trajectories of fluid tracers, and bidisperse heavy particles with and without gravity were calculated from a direct numerical simulation of homogeneous, isotropic turbulence. Particle pair dispersion shows a short-time, ballistic (Batchelor) regime and a transition to super-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…Because, here, we consider clusters with complex shapes and a broad range of sizes, a direct comparison with results obtained for particle-pair dispersion is not straightforward. We notice, however, that the slower separation in presence of gravity is qualitatively consistent with the results of Chang et al (2015). Fourth, and perhaps most striking, the radius of gyration shows only marginal variations during the cluster lifetime, indicating that the relative distance between the particles remains approximately unchanged during the lifetime.…”
Section: Relative Dispersion Of Clustered Particlessupporting
confidence: 87%
See 1 more Smart Citation
“…Because, here, we consider clusters with complex shapes and a broad range of sizes, a direct comparison with results obtained for particle-pair dispersion is not straightforward. We notice, however, that the slower separation in presence of gravity is qualitatively consistent with the results of Chang et al (2015). Fourth, and perhaps most striking, the radius of gyration shows only marginal variations during the cluster lifetime, indicating that the relative distance between the particles remains approximately unchanged during the lifetime.…”
Section: Relative Dispersion Of Clustered Particlessupporting
confidence: 87%
“…only recently (Bec et al 2010;Chang, Malec & Shaw 2015;Bragg et al 2016): its impact on the particle dispersion rate compared to fluid tracers was found to be non-monotonic in time and strongly dependent on the initial separation. Because, here, we consider clusters with complex shapes and a broad range of sizes, a direct comparison with results obtained for particle-pair dispersion is not straightforward.…”
Section: Relative Dispersion Of Clustered Particlesmentioning
confidence: 99%
“…We found that for particles with |∆St| ≥ 0.5, gravity enhances the mean-square separations of the particles both forward in time (FIT) and backward in time (BIT), whereas it suppresses the relative dispersion of weakly bidisperse particles with |∆St| = 0.1. We also observed that the duration over which the particles separate ballistically is much larger when they are subjected to gravity as compared to the case without gravity, as was also observed in [29] for weakly inertial particles. For Froude number F r = 0.052, the vertical relative dispersion is enhanced for the range of Stokes numbers considered, and the enhancement is primarily due to the differential sedimentation of the particles.…”
Section: Discussionsupporting
confidence: 81%
“…This is in contrast to pair or multiparticle dispersion, for which subgrid‐scale velocity fluctuations are important when the initial particle separations are less than the grid scale [ Weil et al , ]. Second, strongly sedimenting particles tend to smooth over small‐scale, high‐frequency velocity fluctuations within the turbulent flow [ Chang et al , ]. The unresolved small scales in the LES are likely to be smoothed over based on the following observations.…”
Section: Model Setup For Lagrangian Ice Particle Tracking In 3‐d Timementioning
confidence: 99%